2009
DOI: 10.1097/mnm.0b013e3283298f90
|View full text |Cite
|
Sign up to set email alerts
|

The role of coughing as a gastroesophageal-reflux provoking maneuver: the scintigraphical evaluation

Abstract: The results of our study showed that 39% (25 of 64) of the observed GER findings were achieved exclusively by means of cough provocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…It has been argued that the combination of primary tracheomalacia with GER could be explained by the presence of certain defects in foregut separation, which leads to esophageal dysmotility 14, 15. It has also been speculated that cough, which occurs frequently in these patients because of trapped airway secretions, can aggravate GER by increasing intrabdominal pressure 16, 17. The wide variations in intrathoracic and intrabdominal pressures (IAP) related to the abnormal physiology of breathing in subjects with tracheomalacia were also stated as a possible mechanism 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that the combination of primary tracheomalacia with GER could be explained by the presence of certain defects in foregut separation, which leads to esophageal dysmotility 14, 15. It has also been speculated that cough, which occurs frequently in these patients because of trapped airway secretions, can aggravate GER by increasing intrabdominal pressure 16, 17. The wide variations in intrathoracic and intrabdominal pressures (IAP) related to the abnormal physiology of breathing in subjects with tracheomalacia were also stated as a possible mechanism 6.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 It has also been speculated that cough, which occurs frequently in these patients because of trapped airway secretions, can aggravate GER by increasing intrabdominal pressure. 16,17 The wide variations in intrathoracic and intrabdominal pressures (IAP) related to the abnormal physiology of breathing in subjects with tracheomalacia were also stated as a possible mechanism. 6 Although a significant increase in transdiphragmatic pressure which overcomes lower esophageal sphincter (LES) pressure, was postulated as the cause of GER, none of these studies were designed to provide the physiological proof for this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few objective studies and no ambulatory studies in children. The sole objective study in children used scintigraphy16 and examined non-spontaneous cough (ie, cough on command). Our current study is the first in children in an ambulatory real-life setting that has quantified the relationship between acid GER episodes and cough objectively.…”
Section: Discussionmentioning
confidence: 99%
“…Few ambulatory studies exist that evaluate the relationship between cough and reflux objectively. Indeed, there are no published ambulatory objective studies in children, and the only objective study in children showed that cough induces reflux 16. All ambulatory objective studies to date have used manometry1720 to quantify cough that is based on alterations in intraoesophageal pressure reflecting the increase in intrathoracic pressures that occur with the expiratory phase of cough.…”
mentioning
confidence: 99%
“…Kronik öksürük epizotları sırasında intraabdominal basınç artarak özellikle bazal alt özofagus sfinkter basıncının düşük olduğu veya hiatal herni varlığında alt özofagus sfinkter basıncını aşabilir. Çocuklarda yeni yapılmış bir sintigrafi çalışmasında klinik olarak reflü şüphesi olan olguların istemli öksürük sırasında %51.6'sında özofageal reflü saptanmıştır [38]. Tüm nedenler göz önüne alındığında reflü durumlarının en sık nedeni TLESR'dır.…”
Section: öKsürük-reflü Mekanizmalarıunclassified